A Case Report : Patent Foramen Ovale Closure in Young Male Patient with Recurrent Cryptogenic Stroke - Kino Kino; Wenny Widyastuti; Denada Florencia Leona (Yayasan Literasi Sains Indonesia, 2022)
Patent foramen ovale is one of the most common congenital abnormalities in children. In PFO, there is a valve-like opening between the atrial septum secundum and primum at the fossa ovalis of the heart. A cryptogenic stroke is a stroke for which no clear cause can be identified. In some cases, the PFO can be wide open, allowing paradoxical embolism to pass from the vein into the arterial circulation, that cause cryptogenic stroke. The prevalence of PFO associated with cryptogenic stroke are relatively high, especially in young age. The thorough evaluation was needed to assure the causative relationship between the PFO and stroke or just a merely coincident, which can help to decide the best treatment strategy. Many studies recommend the closure of PFO in patient with cryptogenic stroke to prevent recurrent incident of stroke. This case report transcatheter PFO closure in a young male patient with history of recurrent stroke after serial examination to evaluate the likelihood of PFO as the cause of his stroke.